The Utilization of Spotify Application to Improve English Listening Skill: Students’ experience - Yanti, Dawi (International Journal of Language and Ubiquitous Learning, 2024)
Background. Listening is a complex skill involving attentive listening, understanding oral symbols, appreciation, content capture, and comprehension of communication through spoken language. It is a fundamental skill in language learning that supports other language abilities. Purpose. This study aims to investigate the utilization of the Spotify application in improving English listening skills among sixth-semester English Tadris students at the Faculty of Tarbiyah and Keguruan, Universitas Islam Negeri Mahmud Yunus Batusangkar. Method. The research employs a quantitative approach with a survey design. Data collection was conducted using a questionnaire comprising 24 statements, distributed to each student in the class. The population consisted of sixth-semester English Tadris students at the university, with a sample size of 37 participants. The questionnaire's reliability was established with an RPB for each item greater than the r table (0.325) and a Cronbach's alpha of 0.831. Results. The assessment results indicate a positive response from students regarding the use of the Spotify application for improving their listening skills. Students reported that various features available on Spotify, along with its accessibility, contributed to enhancing their listening abilities. Conclusion. The study concludes that the Spotify application is a valid and reliable tool for improving students' English listening skills. Its effectiveness is attributed to the diverse features offered by the application and its convenience of use. These findings suggest that Spotify can be a valuable resource for language learners seeking to enhance their listening proficiency.